Of gold and shadows [large type] - Griep, Michelle (Griep, Michelle. Time's lost treasures, 2025)
"In Victorian England, Egyptologist Ami Dalton balances academic life with a covert role rescuing black-market artifacts. Oxford bachelor Edmund Price unexpectedly finds himself entangled with Ami, and as they delve into a newly acquired collection, an artifact rumored to be cursed surfaces, and they wonder if something nefarious is hiding among the shadows"--